Gay and Lesbian Students in Catholic High Schools: A Qualitative Study of Alumni Narratives - Maher, Michael J. (Catholic Education: A Journal of Inquiry and Practice, 2007)
The Catholic Magisterium has made a distinction between homosexual orientation (disordered but not sinful), homosexual activity (sinful, but judged “with prudence”), rights of gay and lesbian people, and the Church’s pastoral responsibilities to gay and lesbian people. Both the Vatican and the American bishops have clearly stated that the topic of homosexuality must be addressed in Catholic education, but the emphases on how it is addressed differ between the Vatican (emphasis on finding causes and cures) and the American bishops (providing pastoral care and inclusion). This article deals with the experiences of gay and lesbian youth in Catholic high schools. It is based on in-depth interviews with 25 (12 female and 13 male) gay and lesbian alumni who attended Catholic high schools in the 1980s and 1990s. What emerged is a theme of “disintegration.” Things simply did not fit together in their lives in the areas of family, peers, school, spirituality, and identity. This is in stark contrast with Catholic teaching, which proposes that the purpose of Catholic education is the integration of all these areas.